2001
DOI: 10.1016/s0960-9822(01)00095-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric spindle pole localization of yeast Cdc15 kinase links mitotic exit and cytokinesis

Abstract: The inactivation of mitotic cyclin-dependent kinases (CDKs) during anaphase is a prerequisite for the completion of nuclear division and the onset of cytokinesis [1, 2]. In the budding yeast Saccharomyces cerevisiae, the essential protein kinase Cdc15 [3] together with other proteins of the mitotic exit network (Tem1, Lte1, Cdc5, and Dbf2/Dbf20 [4-7]) activates Cdc14 phosphatase, which triggers cyclin degradation and the accumulation of the CDK inhibitor Sic1 [8]. However, it is still unclear how CDK inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 24 publications
2
92
0
Order By: Relevance
“…Despite Cdc15 protein being present at constant levels throughout the cell cycle , we and others found that Cdc15 only localized to SPBs during anaphase and telophase (Cenamor et al, 1999;Gruneberg et al, 2000;Xu et al, 2000;Menssen et al, 2001). However, there are slight variations in the localization pattern observed for Cdc15, which appears to depend on the epitope tag used in the different studies.…”
Section: The Localization Of Cdc15mentioning
confidence: 49%
See 2 more Smart Citations
“…Despite Cdc15 protein being present at constant levels throughout the cell cycle , we and others found that Cdc15 only localized to SPBs during anaphase and telophase (Cenamor et al, 1999;Gruneberg et al, 2000;Xu et al, 2000;Menssen et al, 2001). However, there are slight variations in the localization pattern observed for Cdc15, which appears to depend on the epitope tag used in the different studies.…”
Section: The Localization Of Cdc15mentioning
confidence: 49%
“…Several reports had shown that Cdc15 localizes to SPBs (Cenamor et al, 1999;Xu et al, 2000;Gruneberg et al, 2000;Menssen et al, 2001). However, slight differences in the dynamics of Cdc15 localization had been observed, depending on the epitope tag used.…”
Section: Cdc15 Localizes To Both Spindle Pole Bodies During Anaphasementioning
confidence: 99%
See 1 more Smart Citation
“…Besides their roles in mitotic exit, components in the MEN such as Cdc5, Tem1, Cdc15, Dbf2-Mob1, and Cdc14 are required for proper actin ring formation at the mother-bud-neck (Jimenez et al, 1998;Frenz et al, 2000;Lee et al, 2001). Consistent with their roles in cytokinesis, both Cdc15 and Dbf2-Mob1 localize to the bud-neck in late mitosis following the downregulation of Cdk1 activity (Xu et al, 2000;Luca et al, 2001;Menssen et al, 2001;Bardin et al, 2003;Lim et al, 2003). Unlike Cdc15 and Dbf2, however, Cdc5 localizes to the neck as early as G2 (prior to Cdc28 downregulation) and remains at this structure until late mitosis , suggestive of additional role(s) at the neck.…”
Section: Cytokinesismentioning
confidence: 97%
“…Nevertheless, recent evidence suggests that MEN signalling components have more direct roles in orchestrating the process of cytokinesis. On one hand, Dbf2p and Mob1p have been found at the actin-myosin ring (AMR) structure that is essential for abscission [35][36][37][38], and Cdc15p, Dbf2p and Mob1p are required for AMR contraction [39,40]. Moreover, current evidence suggests that the MEN components Dbf2p and Mob1p can regulate the cytokinetic components Chs2p, Hof1p, and Inn1p (summarised in [33,41]).…”
Section: Mitotic Exit Network (Men) In S Cerevisiaementioning
confidence: 99%